An Analysis Of Speaking Anxiety In Efl Students Presentation At Twelve Grade Of Smk Al-Furqon Bondowoso In 2020/2021 Academic Year - Waskito, Padar; Mufaridah, fit; Nurkamilah, Nurkamilah (Universitas Muhammadiyah Jember, 2023)
Speaking as performance refers to public speaking such as, presentation, speeches, news casters, host and presenter which is giving an information to the audience. There are four theory base of communicative language teaching, Language s a system for the expression of meaning, The primary function of language is for interaction and communication, The structure of language reflects its functional and communicative uses, The primary units of language are not merely its grammatical and structural features. The researcher try to find out about speaking anxiety and the factor causing speaking anxiety in Students Presentation at twelve grades of SMK Al-Furqon Bondowoso in the 2020//2021 academic year. In this research A qualitative study is intended for collecting information about the status of an existing indication. Limited vocabulary included external factor because the loading factor with a strong external factor that its score 67% and the number of limited vocabulary was the second higher after embarrassment. It means that limited vocabulary was the second highest score on external factor that influenced student anxiety to speaking English. Motivation included internal factor because the loading factor with a strong internal factor than its score was 71% and the number of motivation was higher than all of internal factors. Based on the results of the analysis, there are two factors influencing students’ anxiety in speaking English that internal and external factors.